Le soliloque un élément cathartique, dans Je Suis Seul de Mbarek Ould Beyrouk - Houari BENALLA; Fatiha CHAOUIB (Altralang Journal)
ABSTRACT: This article suggests a reflection on the soliloquy of the sole protagonist of the novel and the therapeutic virtue of being locked up in Mbarek Ould Beyrouk’s “I am Alone”. We will see how the soliloquy and the confinement of the narrator/main character had a cathartic function, fully ensuring his psychological evolution following the questioning of his whole life, as well as the transition from negative heroes (antiheroes) to positive heroes. In short, a solilocutous word that provides relief and a confinement that becomes deliverance.